TRANSFORMASI IMAN DALAM KEHIDUPAN GEREJA PERDANA MENUJU GEREJA SINODAL: DALAM BINGKAI TEPAS DAN ARDAS KEUSKUPAN KETAPANG - Petrus Riyant; Gabriel Bala (Aggiornamento, 2022)
The focus of this research is to highlight the progress of the times that have had a significant impact on the life of the vocation and proclamation of the Church's faith. in Ketapang Diocese. The purpose of this research is to see to what extent the spirit of the unity of the Synodal Church in the Dioceses has become a collective movement. As in the motto of KV II: Ecclesia semper Reformanda, it would be a trumpet for transformation. Therefore, this study seeks to explore and gain access to the spirit of transformation of the faith life of the congregation since the early church until now in its relationship as a synodal church. The methodology used is to collect primary and secondary data. Primary data were obtained through the results of TEPAS (Pastoral Meeting) as well as ARDAS (Basic Directions) of Ketapang Diocese which were promulgated from 2021-2033. On the other hand, secondary data is related to literature that supports the research topic. The results of the research found that the Synodal Church has indeed become a joint movement of the Universal Church which is very relevant with the times. The relevance of the Synodal Church to the Diocese is the transformation of faith that goes together in a spirituality of unity towards salvation.